Developing A Nigerian Local Government Through Economic Gardening: A Roadmap - Umaru Mustapha Zubairu; Ruth Kolo; Hadiza Umar; Asma'u Usman; Yakubu Mustapha; Jaafar Umar (LPPM of NAROTAMA UNIVERSITY, 2019)
Economic Gardening is an innovative economic development strategy whereby local businesses are fostered and encouraged, and the skills of local workers are upgraded. Since its inception in Littleton, Colorado in 1989, this concept has been put forward by various scholars as a viable and more sustainable economic development strategy than the traditional business attraction strategy. Various implementation experiences have provided further evidence of its effectiveness in improving the quality of life of the inhabitants of a community. This paper charts a roadmap for the development and future implementation of an economic gardening strategy for a Nigerian local government whose officials have shown an interest in adopting such a strategy. A seven-step process was adopted from a review of economic gardening scholarship: 1) Working hand-in-hand with local government officials and other stakeholders, 2) Identifying the community’s assets, 3) Developing a collaborative effort amongst all stakeholders, 4) Developing a clear and transparent operating agreement, 5) Identifying the key targets for services, 6) Developing an effective way to deliver these services, and 7) Communicating regularly with the community so as to gain and retain their support. A lack of political will and a lack of adequate infrastructure were identified as the two biggest obstacles to the successful implementation of the economic gardening strategy in the local government. The first obstacle was mitigated by the fact that it was the local government officials who approached our team to develop the strategy, whilst the second obstacle was mitigated by a proposal for the development of a solar farm within the local government via a public-private partnership with an international solar firm. It is hoped that a successful implementation of this strategy will improve the lives of the inhabitants of the local government and serve as an example for other Nigerian local governments.